Implementation of the Inquiry Model on the Critical Thinking Ability of Prospective Physical Education Teachers in Football Learning - Hadiana, Oman; Syamaun, Muzakkir; Hamid, Arhamni Binti; Ratnawati, Ratnawati (Department of Physical Education, Faculty of Health Sciences, Universitas Jenderal Soedirman, 2023)
Physical education is not just about learning skills from several basic techniques in sports including football. Currently, football needs to be supported by critical thinking skills to produce a more focused and efficient game. The aim of this research is to implement an inquiry learning model on students critical thinking skills in the game of football in the aspects of maintaining possession of the ball, creating space in attack, and shooting the ball into the goal. The method used was an experiment with The Randomized Posttest Only Control Group Design. The total sample was 70 students divided into two groups, namely the experimental group of 35 people who were given inquiry model treatment and the control group of 35 people who were given conventional model treatment. The instrument for measuring critical thinking skills uses an observation sheet whose level of validity has been tested. The results of the research show that students critical thinking abilities for the inquiry model in football learning in the aspect of maintaining possession of the ball are in the very good category, while for the conventional model in this aspect they are in the good category. Students critical thinking skills for the inquiry model for the aspect of creating space in attack are in the very good category, while for the conventional model in this aspect they are in the good category. Students critical thinking skills for the inquiry model in the aspect of shooting the ball into the goal are in the very good category, while for the conventional model in this aspect they are in the good category. The application of the inquiry model for students as prospective physical education teachers in order to improve critical thinking skills in football game material has a significant impact.